The merger [videorecording (DVD)] - Callinan, Damian; Callinan, Damian; Howard, John, 1952-; Mulvany, Kate (Indiepix Films, 2023)
A former star footballer turned social justice campaigner returns to his home town, befriends a young wannabe filmmaker who recently lost his father and is persuaded, despite opposition, into coaching the town's struggling footy team. He recruits refugees to make up the numbers with hilarious results, taking the community on a journey of change.